Symbolic Attack Sites and the Performance of Terrorism, Counter Terrorism and Memory - Aly, Anne (RMIT, 2014)
This paper reports on a project that explores how terrorist attack sites become communicative platforms within which three kinds of enactment- the terrorist attack, counter measures by the state and affective public responses- construct narratives and counter narratives about terrorism. This approach is applied in research project that explores the range of meanings that emerge around the site of the 2002 Bali Bombings in Kuta, the political nature of commemoration and the ways in which victims voices become part of the narrative/counter narrative of violent extremism. The conceptual framework applied in this research incorporates performance theory and notions of the audience (government and publics) as narrators in a discourse of contested meanings that are also enacted through the symbolic imagery of the attack site. The findings reported here demonstrate how attack sites become dynamic spaces for the interpretation and reinterpretation of meanings about terrorism embodied in the narratives generated by the performance roles of various actors. These meanings challenge the performative power of the terrorist attacks but also construct counter narratives to official responses to terrorism.